Effect of resveratrol treatment on graft revascularization after islet transplantation in streptozotocin-induced diabetic mice. Issue 1 (2nd January 2018) - Lee, Eun-Mi; Park, Inwon; Lee, Ye-Jee; You, Young-Hye; Kim, Ji-Won; Kim, Myung-Jun; Ahn, Yu-Bae; Kim, Pilhan; Ko, Seung-Hyun
ABSTRACT: We evaluated the effect of resveratrol (RSV) on graft survival after islet transplantation (ITx) in diabetic mice. Isolated islets from Balb/c mice (200 IEQ) were transplanted under the kidney capsule of diabetic Balb/c mice. Vehicle or RSV (200 mg/kg/day, orally) was given for 14 days after ITx. Two more control groups [STZ-treated (No-ITx-Control) and STZ+RSV-treated (No-ITx-RSV) mice without ITx] were added. Glucose tolerance tests (GTT) was performed at 14 days after ITx. In vitro, isolated islets pretreated with vehicle or RSV (1 μM) were incubated in a hypoxic chamber (O2 1%, 1hr). Some of the ITx was performed in mouse insulin 1 gene promoter-green fluorescent protein (MIP-GFP) transgenic mice and analyzed using an in vivo imaging system. After 14 days of ITx, 2-hr glucose levels on GTT in the RSV-treated group were significantly lower than those of other control groups. But the glucose status was not improved in No-ITx mice with RSV. At day 3, the percentage of Ki-67/insulin co-stained cells in islet graft was significantly increased in the RSV-ITx group. Immunostaining with anti-insulin and anti-BS-1 antibodies revealed significantly higher insulin-stained area and vascular density in RSV-treated islet grafts. The mean vessel volume per islet graft measured by in vivo imaging was significantly higher in the RSV-treated group at day 3. In isolated islets cultured in hypoxic conditions, the cell death rate and oxidative stress were significantly attenuated with RSV pretreatment. Hypoxic treatment for isolated islets decreased the expression of SIRT-1 mRNA, and this attenuation was recovered by RSV pretreatment. Our data suggest that RSV treatment improved glycemic control, beta-cell proliferation, reduced oxidative stress, and enhanced islet revascularization and the outcome of ITx in diabetic mice.